KONSEP KONSTITUSI HIJAU (GReeN CoNSTITUTIoN) DALAM KEGIATAN EKONOMI BERKELANJUTAN - Yunizar Prajamufti, Jundiani, (Fakultas Syariah, 2011)
object of this research addresses the problem of green constitution concept management in supporting sustainable economic activities. This research applies normative law approach. The result shows that the character of green constitution concept management in running economic activities refers to the essence of human life in nation and state living context which is in line with the five basic principles keeping balance and harmonious relationship with nature. It is the implication of principles in running economic activities based on article 33 of Indonesia State constitution 1945 on forming economic law of Indonesia. hence, it has been a basic change on perception and national development concept which is integrated with sustainable development .As a result, that condition needs a new pattern towards the establishment of sustainable development economic law. Â obyek kajian penelitian ini mengangkat permasalahan karakteristik pengaturan konsep konstitusi hijau (green constitution) dalam mendukung penyelenggaraan kegiatan ekonomi yang berkelanjutan dan implikasi prinsip-prinsip penyelenggaraan kegiatan ekonomi sebagaimana yang termuat dalam UUD 1945. Metode penelitian menggunakan pendekatan juridis normative. hasil penelitian menunjukan karakteristik pengaturan konsep green constitution dalam penyelenggaraan kegiatan ekonomi merujuk pada hakikat kehidupan manusia dalam kehidupan berbangsa dan bernegara Pancasila yang senantiasa menjaga hubungan yang selaras dan seimbang dengan alam. hal tersebut berimplikasi prinsip-prinsip penyelenggaraan kegiatan ekonomi menurut Pasal 33 UUD 1945 yaitu telah dilakukan perubahan yang mendasar pada cara pandang dan konsep pembangunan nasional yang terintegrasi sehingga dibutuhkan pola baru menuju penormaan hukum ekonomi berkelanjutan.